Civilisations in dialogue? UNESCO and the politics of building East and West relations. Issue 3 (16th April 2022) - Winter, Tim
ABSTRACT: UNESCO's long-standing commitment to peace and international solidarity has been developed through various projects designed to foster dialogue and mutual respect between East and West. Such ideas were critically important during the Cold War, as different initiatives separated by three decades spoke to the geopolitics of the moment. It is within this context that we need to consider UNESCO's new commitment to Silk Road multilateralism, the forces driving it, and the stakes. This paper takes up such themes by considering the international cultural politics at play in fostering 'mutual understanding' between East and West and why a return to civilisational discourses matter at a time when global power is moving to the East.